2018
DOI: 10.1103/physrevb.97.235430
|View full text |Cite
|
Sign up to set email alerts
|

Band alignment at Ag/ZnO(0001) interfaces: A combined soft and hard x-ray photoemission study

Abstract: Band alignment at the interface between evaporated silver films and Zn-or O-terminated polar orientations of ZnO is explored by combining soft and hard X-ray photoemissions on native and hydrogenated surfaces. Ultraviolet Photoemission Spectroscopy (UPS) is used to track variations of work function, band bending, ionization energy and Schottky barrier during silver deposition.The absolute values of band bending and the bulk position of the Fermi level are determined on continuous silver films by HArd X-ray Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 124 publications
(214 reference statements)
3
15
0
Order By: Relevance
“…% AZO films, respectively. These values are consistent, in absolute value, to what happens in other metal NPs/ZnO 71 , 72 and similar Au NPs/oxide systems 73 , 74 and can be sustained by the substrate due to the small volume of Au NPs with respect to the film volume. Increasing further the dopant concentration above the optimal doping condition (4 at.…”
Section: Resultssupporting
confidence: 82%
“…% AZO films, respectively. These values are consistent, in absolute value, to what happens in other metal NPs/ZnO 71 , 72 and similar Au NPs/oxide systems 73 , 74 and can be sustained by the substrate due to the small volume of Au NPs with respect to the film volume. Increasing further the dopant concentration above the optimal doping condition (4 at.…”
Section: Resultssupporting
confidence: 82%
“…Chernysheva et al have shown the shift in Fermi level of ZnO by B0.04 eV on the Ag/ZnO contact. 65 The work functions for Ag (F M = 4.26 eV) and ZnO (F S = 5.2 eV) have been adopted from the reference of Zheng et al 56 where V 0 defines the defect level and E g the band gap of the semiconductor layer. Adsorbates modify the ionization energy and induce a change in band bending for a perfect Schottky contact (where, F SB is the Schottky barrier of the interface), and construct the interface levels, from which the transition can be shown.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorbates modify the ionization energy and induce a change in band bending for a perfect Schottky contact (where, F SB is the Schottky barrier of the interface), and construct the interface levels, from which the transition can be shown. 65 The change in the ionization energy with the increasing concentration of Ag on ZnO can be expressed as DI = Dw = eNp > (y)/e 0 , where, e is the electronic charge, N the number of dipoles and p > (y) the perpendicular polarisation through the adsorbate layer. Thus, with the increase in the Ag concentration around ZnO, both of the effects lead to the decrease the difference in valence and conduction bands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Chemistry and structure of Cr/alumina Occurring in supported clusters 25 , the Cr 2p 3/2 shifts could involve a final state screening of the positive photo-hole [60][61][62][63] ; an estimate is given by E F,m = αe 2 /4πε 0 R, where R is the particle radius, ε 0 the vacuum permittivity and α a parameter around 0.5 61,62 , so that the observed shift of ∼ 1 eV could stem from clusters of around 1.5 nm in size. However, several arguments favour chemistry instead of electrostatics.…”
Section: Computational Detailsmentioning
confidence: 99%